Efficacy and safety of ultra-short wave diathermy on COVID-19 pneumonia: a pioneering study - Huang, Liangjiang; Li, Qian; Shah, Sayed Zulfiqar Ali; Nasb, Mohammad; Ali, Iftikhar; Chen, Bin; Xie, Lingfeng; Chen, Hong (Frontiers in Medicine, 2023)
Background The ultra-short wave diathermy (USWD) is widely used to ameliorate inflammation of bacterial pneumonia, however, for COVID-19 pneumonia, USWD still needs to be verified. This study aimed to investigate the efficacy and safety of USWD in COVID-19 pneumonia patients. Methods This was a single-center, evaluator-blinded, randomized controlled trial. Moderate and severe COVID-19 patients were recruited between 18 February and 20 April 2020. Participants were randomly allocated to receive USWD + standard medical treatment (USWD group) or standard medical treatment alone (control group). The negative conversion rate of SARS-CoV-2 and Systemic Inflammatory Response Scale (SIRS) on days 7, 14, 21, and 28 were assessed as primary outcomes. Secondary outcomes included time to clinical recovery, the 7-point ordinal scale, and adverse events. Results Fifty patients were randomized (USWD, 25; control, 25), which included 22 males (44.0%) and 28 females (56.0%) with a mean (SD) age of 53 ± 10.69. The rates of SARS-CoV-2 negative conversion on day 7 (p = 0.066), day 14 (p = 0.239), day 21 (p = 0.269), and day 28 (p = 0.490) were insignificant. However, systemic inflammation by SIRS was ameliorated with significance on day 7 (p = 0.030), day 14 (p = 0.002), day 21 (p = 0.003), and day 28 (p = 0.011). Time to clinical recovery (USWD 36.84 ± 9.93 vs. control 43.56 ± 12.15, p = 0.037) was significantly shortened with a between-group difference of 6.72 ± 3.14 days. 7-point ordinal scale on days 21 and 28 showed significance (p = 0.002, 0.003), whereas the difference on days 7 and 14 was insignificant (p = 0.524, 0.108). In addition, artificial intelligence-assisted CT analysis showed a greater decrease in the infection volume in the USWD group, without significant between-group differences. No treatment-associated adverse events or worsening of pulmonary fibrosis were observed in either group. Conclusion Among patients with moderate and severe COVID-19 pneumonia, USWD added to standard medical treatment could ameliorate systemic inflammation and shorten the duration of hospitalization without causing any adverse effects. Clinical Trial Registration: chictr.org.cn, identifier ChiCTR2000029972.